VOZES DOCENTES: ANÁLISE DE REFLEXÕES DE PROFESSORES DE CIÊNCIAS SOBRE SUA VIVÊNCIA PROFISSIONAL - Maria Cristina Doglio Behrsin (Ensaio Pesquisa em Educação em Ciências, 2011)
The present text shows some reflections made during the accomplishment of a research regarding the graduation of teachers, whose object of studies was established around the elements of the teaching journey of six Science teachers. The mentioned research had as a point of confluence the histories of the professional life of these teachers, its participation in a course of Post Graduation in Science Teaching. From the reports onwards, one sought to identify the approximations and distances in its perceptions about the school, the Education and the work of teaching, establishing a dialogue among the protagonists of the research and among the several authors who examined the questions recurrent of these speeches, intending, therefore, to give some contributions to the discussion.